Identification of a number of phenolic compounds in grape seed extract tablets by high-performance liquid chromatography - محمد, ليث; ديمة دياب; نزار عيسى (Latakia University Journal -Medical Sciences Series, 2024)
Grape seed extract (GSE) is a dietary supplement made by removing, drying, and pulverizing the bitter-tasting seeds of grapes, Grape seeds are rich in antioxidants, including phenolic acids, anthocyanin's, flavonoids, and oligomeric proanthocyanidin complexes (OPCs), Due to its high antioxidant content, GSE can help prevent disease and protect against oxidative stress, tissue damage, and inflammation. The importance of this research comes from the growing popularity and use of grape seed supplements globally, and the health benefits they provide by possessing antioxidant and anti-inflammatory activity, Therefore, this study aims to extract the phenolic compounds present in a locally marketed grape seed extract preparation and to determine the identity of a number of phenolic compounds by high-performance liquid chromatography. This study found that locally marketed grape seed extract is rich in many phenolic compounds, the most important of which are quercetin, caffeic, sinapic, catechin, and small concentrations of gallic and ferulic acid. Therefore, we recommend conducting a complete identification of phenolic compounds due to the presence of many important phenolic compounds that have not been identified.